Preparation and characterization of a new bio nanocomposites based poly(glycerol sebacic‐urethane) containing nano‐clay (Cloisite Na+) and its potential application for tissue engineering. Issue 10 (20th April 2022) - Jaberi, Navid; Fakhri, Vafa; Zeraatkar, Ali; Jafari, Aliakbar; Uzun, Lokman; Shojaei, Shahrokh; Asefnejad, Azadeh; Faghihi Rezaei, Vahid; Goodarzi, Vahabodin; Su, Chia‐Hung; Ghaffarian Anbaran, S. Reza
Abstract: Nanocomposites containing clay nanoparticles often present favorable properties such as good mechanical and thermal properties. They frequently have been studied for tissue engineering (TE) and regenerative medicine applications. On the other hand, poly(glycerol sebacate) (PGS), a revolutionary bioelastomer, has exhibited substantial potential as a promising candidate for biomedical application. Here, we present a facile approach to synthesizing stiff, elastomeric nanocomposites from sodium‐montmorillonite nano‐clay (MMT) in the commercial name of Cloisite Na + and poly(glycerol sebacate urethane) (PGSU). The strong physical interaction between the intercalated Cloisite Na + platelets and PGSU chains resulted in desirable property combinations for TE application to follow. The addition of 5% MMT nano‐clay resulted in an over two‐fold increase in the tensile modulus, increased the onset thermal decomposition temperature of PGSU matrix by 18°C, and noticeably improved storage modulus of the prepared scaffolds, compared with pure PGSU. As well, Cloisite Na + enhanced the hydrophilicity and water uptake ability of the samples and accelerated the in‐vitro biodegradation rate. Finally, in‐vitro cell viability assay using L929 mouse fibroblast cells indicated that incorporating Cloisite Na + nanoparticles into the PGSU network could improve the cell attachment and proliferation, rendering the synthesized bioelastomers potentially suitable for TE and regenerative medicine applications. Abstract : The role of Nanoclay as a natural nanoparticles for increasing mechanical and bio‐properties of PGSU material.